2016
DOI: 10.1097/mpg.0000000000001174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intestinal Function in Children With Autism and Gastrointestinal Symptoms

Abstract: The present study supports the observation that children with autism who have symptoms of gastrointestinal disorders have objective findings similar to children without autism. Neither noninvasive testing nor endoscopic findings identify gastrointestinal pathology specific to autism, but may be of benefit in identifying children with autism who have atypical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 25 publications
1
60
1
Order By: Relevance
“…This finding was not supported by extensive observations of Kushak et al[37] from a center that performs many intestinal biopsies. These investigators had originally found that more than half of a group of children with autism had low levels of the enzyme lactase in duodenal biopsies[38].…”
Section: Inflammation Hypothesiscontrasting
confidence: 56%
“…This finding was not supported by extensive observations of Kushak et al[37] from a center that performs many intestinal biopsies. These investigators had originally found that more than half of a group of children with autism had low levels of the enzyme lactase in duodenal biopsies[38].…”
Section: Inflammation Hypothesiscontrasting
confidence: 56%
“…Subsequently, IL-1β and TNF-α bind to brain endothelial cells and induce immune responses in the brain (Li et al, 2009b; Ashwood et al, 2011; de Theije et al, 2011). Alterations in the composition of the gut microbiota and their metabolic products are commonly observed in patients with ASD and in animal models of ASD (de Magistris et al, 2010; Borre et al, 2014; Kushak et al, 2016). Hsiao et al observed gastrointestinal barrier defects and microbiota alterations in a mouse model displaying features of ASD.…”
Section: Relationship Between Asd and Gut Microbiotamentioning
confidence: 99%
“…Except of the leaky gut, it may be other factors that are the cause of abnormal signalling from intestines to the brain. Major role is attributed to the abnormal composition of gut microbiota that was observed in individuals with ASD, also intestinal inflammation and upregulation of proinflammatory cytokines in the gut mucosa of children with ASD has been reported (Van De Sande et al 2014, Kushak et al 2016 Moreover, increasing intestinal cytokine levels were associated with more impaired communication and aberrant behaviors (Ashwood et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…It is believed that FC is an under-appreciated marker with potential to serve as a diagnostic and follow-up tool for other gastrointestinal (GI) conditions. It has been studied as a potential marker of intestinal inflammation also in ASD (Fernell et al 2007, De Magistris et al 2010, Pusponegoro et al 2015, Kushak et al 2016.…”
Section: Introductionmentioning
confidence: 99%